Probing substrate binding to Metallo-β-Lactamase L1 from Stenotrophomonas maltophilia by using site-directed mutagenesis - Carenbauer, Anne L (BioMed Central, 2002)
BACKGROUND: The metallo-β-lactamases are Zn(II)-containing enzymes that hydrolyze the β-lactam bond in penicillins, cephalosporins, and carbapenems and are involved in bacterial antibiotic resistance. There are at least 20 distinct organisms that produce a metallo-β-lactamase, and these enzymes have been extensively studied using X-ray crystallographic, computational, kinetic, and inhibition studies; however, much is still unknown about how substrates bind and the catalytic mechanism. In an effort to probe substrate binding to metallo-β-lactamase L1 from Stenotrophomonas maltophilia, nine site-directed mutants of L1 were prepared and characterized using metal analyses, CD spectroscopy, and pre-steady state and steady state kinetics. RESULTS: Site-directed mutations were generated of amino acids previously predicted to be important in substrate binding. Steady-state kinetic studies using the mutant enzymes and 9 different substrates demonstrated varying K(m) and k(cat) values for the different enzymes and substrates and that no direct correlation between K(m) and the effect of the mutation on substrate binding could be drawn. Stopped-flow fluorescence studies using nitrocefin as the substrate showed that only the S224D and Y228A mutants exhibited weaker nitrocefin binding. CONCLUSIONS: The data presented herein indicate that Ser224, Ile164, Phe158, Tyr228, and Asn233 are not essential for tight binding of substrate to metallo-β-lactamase L1. The results in this work also show that K(m) values are not reliable for showing substrate binding, and there is no correlation between substrate binding and the amount of reaction intermediate formed during the reaction. This work represents the first experimental testing of one of the computational models of the metallo-β-lactamases.